Do Flipped Learning and Adaptive Instruction Improve Student Learning Outcome? A Case Study of a Computer Programming Course in Taiwan - Chen, Hong-Ren; Hsu, Wen-Chiao (Frontiers in Psychology, 2022)
Flipped learning could improve students' learning effectiveness. However, some studies have pointed out the limitations related to flipped classrooms because the content of the flipped course does not vary according to the needs of the students. On the other hand, adaptive teaching, which customizes the learning mode according to the individual needs of students, can make up for some of the shortcomings of flipped teaching. This study combines adaptive teaching with flipped teaching and applies it to face-to-face classroom activities. The purpose of this research is to explore whether the implementation of flipping and adaptive learning in computer programming course can improve students' learning effectiveness. The experimental subjects of this study are the sophomore students in the Department of Information Management. The flipped classroom with adaptive instruction has realized in the limited course time. This study uses questionnaires to collect pre- and post-test data on students' "learning motivation". The learning effectiveness was evaluated based on the students’ previous programming course (C language) and the semester scores of this course. Research results show that the post-test "learning motivation" has improved overall compared with the pre-test, and the learning effect is also significant. The research results of this research not only prove the effectiveness of modern teaching theories in programming courses, but also lay the foundation for future teaching design.